CHOSEN ASPECTS OF MECHANIZATION OF AGRICULTUREIN INDIVIDUAL FARMS OF MALOPOLSKA - Monika Zioło; Elżbieta Badach; Lidia Luty (Annals of the Polish Association of Agricultural and Agribusiness Economists)
The purpose of this paper was to present results of the surveys according to opinions of Malopolska’sagricultural farms’ owners about amount and age of machines working in those holdings. The researchincluded size of the farms and type of specialization. The analysis was conducted among 144 individual farmowners in 2017 year. According to surveyed people after integration with UE the advantage in investmentin polish agriculture occurred, many farmers have bought tillage units, which are not older than 10 years.Almost 60% handling machinery, cold stores and vans in surveyed Malopolska farms are new, boughtnot later than 10 years ago. Among the oldest machines there are combine harvesters, on average theirage is 15, but 30% of respondents owned machines which had over 20 years. Most respondents think thattheir farms are sufficiently or even well equipped with the requisite equipment, nevertheless they plan topurchase used equipment.